Enhancing Early Childhood Green Awareness via Digital Platform: A Pangandaran Study - Ajeng Mayang; Yudi Barnadi; Ase Suryana; Neris Peri Ardiansyah (Brilliance: Research of Artificial Intelligence, 2025)
Global environmental issues, particularly the energy crisis and climate change, require an active and sustainable educational response. Early Childhood Education (ECE) plays a crucial role in fostering environmental awareness and shaping values and understanding of renewable energy from an early age. In coastal areas like Pangandaran, Indonesia—which has abundant potential for environmentally friendly energy sources such as solar, wind, and biomass—it is essential for communities to begin utilizing these resources sustainably. However, the implementation of this concept in ECE settings remains limited, mainly due to inadequate facilities and a lack of suitable teaching methods. As a strategic measure, the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), through the Education Standards, Curriculum, and Assessment Agency (BSKAP), issued a regulation in 2023 mandating the integration of climate change issues into curricula at all educational levels, including ECE. This policy also supports teacher training programs to enable structured teaching of green energy topics. The main challenge lies in delivering complex material in a way that aligns with the developmental stage of early childhood, which is characterized by exploration and emotional learning. This study explores the effectiveness of a digital-based approach in supporting ECE teachers in Pangandaran by utilizing platforms such as Google Spaces and Learning Management Systems (LMS). This approach is designed to help teachers present renewable energy concepts in a fun, interactive, and age-appropriate manner, thereby enhancing both teachers' and students' understanding and active engagement with environmental issues.